Развитие подхода к моделированию процесса получения этилбензола - Долганова И. О. Ирэна Олеговна; Долганов И. М. Игорь Михайлович; Ивашкина Е. Н. Елена Николаевна; Иванчина Э. Д. Эмилия Дмитриевна (Химия, 2012)
Заглавие с титульного листа